The Grey Falcon: The Life and Teaching of Shaykh ʿAbd al-Qādir al-Jīlānī. - Hamza Malik (Islamic History and Civilization, 2019)
In The Grey Falcon , Hamza Malik offers an account of the life and teaching of the twelfth century scholar and Sufi of Baghdad, and eponym of the Qadiri order, Shaykh ʿAbd al-Qādir al-Jīlānī (1077-1166). The question of whether Jīlānī was a Sufi, or simply a scholar appropriated by later Sufis as has been sometimes suggested, is tackled through an analysis of his three most popular works, the Ghunya li Ṭālibī Ṭarīq al-Ḥaqq , the Futūḥ al-Ghayb , and the Fatḥ al-Rabbānī . Malik identifies and presents Jīlānī's Sufi thought and theological stance, and furthermore attempts to paint a picture of the character and personality of Jīlānī, as might be ascertained solely from the works analysed.